Vasa vasorum in ateroskleroza koronarnih arterij - Hojs, Nina (Medicinski razgledi, 2008)
Vasa vasorum ("vessels of the vessel) are arterioles, capillaries and venules that nourish large arteries and veins. They are derived either from the main blood vessel itself in the case of arteries, and for veins from adjacent arteries as venous vasa vasorum. Atherosclerosis is a systemic dysfunctional endothelial, chronic inflammatory, fibro-proliferative, prothrombotic, angiogenic, multifactorial disease of the arterial intima caused by the retention of modified low-density lipoproteins, along with hemodynamic and redox stress. The first condition for the development of atherosclerosis involves high LDL cholesterol blood levels. The infiltration, retention and modification of excess LDL cholesterol in the arterial intima cause the induction of endothelial cells and consecutive migration of leukocytes into the subendothelial space. Macrophages and lymphocytes inside the arterial intima cause inflammation and tissue damage. A plaque forms, and the thickening of the intima leads to hypoxia and consecutive angiogenesis. Newly formed vasa vasorum destabilize the plaque and cause progression of atherosclerosis. An unstable plaque can rupture and this is strongly associated with vascular occlusion, myocardial ischemia, and infarction. However, vasa vasorum play a positive role when it comes co the regression of atherosclerosis as they may provide a pathway for the removal of incimal fat. Many questions are raised about the best treatment for atherosclerosis.'fbe beneficial effects of statins have already been proven, while other attractivefuture treatments comprise powerful immunosuppressive and antiinflammatory agents, therapeutic angiogenesis and anti-angiogenesis. Finally, vaccination is also an attractive approach to induce protective immunity.
Keywords: Coronary Arteriosclerosis; Vnetje; Vasa Vasorum; Koronarna arterioskleroza; Inflammation; Neovaskularizacija fiziološka; Neovascularization, Physiologic; Vaza vazorum; ožilje; koronarne arterije; ateroskleroza; vnetja